Cycloadditions to Epoxides Catalyzed by Group III–V Transition‐Metal Complexes. Issue 13 (25th May 2015) - D'Elia, Valerio; Pelletier, Jérémie D. A.; Basset, Jean‐Marie
Abstract Complexes of group III–V transition metals are gaining increasing importance as Lewis acid catalysts for the cycloaddition of dipolarophiles to epoxides. This review examines the latest reports, including homogeneous and heterogeneous applications. The pivotal step for the cycloaddition reactions is the ring opening of the epoxide following activation by the Lewis acid. Two modes of cleavage (CC versus CO) have been identified depending primarily on the substitution pattern of the epoxide, with lesser influence observed from the Lewis acid employed. The widely studied cycloaddition of CO2 to epoxides to afford cyclic carbonates (CO bond cleavage) has been scrutinized in terms of catalytic efficiency and reaction mechanism, showing that unsophisticated complexes of group III–V transition metals are excellent molecular catalysts. These metals have been incorporated, as well, in highly performing, recyclable heterogeneous catalysts. Cycloadditions to epoxides with other dipolarophiles (alkynes, imines, indoles) have been conducted with scandium triflate with remarkable performances (CC bond cleavage).